Street Art: Rhetoric, Poetics, Memory and Creativity in the Transmedia Age: The rhetorical figures in the actions of Street art - Morán Fuertes, Asier (Street Art & Urban Creativity, 2025)
The interrelationship between rhetoric, poetics, attention capture, creativity and memory (in the transmedia age) is examined through an analysis of the 107 street art interventions awarded either gold or special prizes between 1999 and 2024 at leading international advertising festivals. The findings are compared with the knowledge derived from the scientific documentary sources consulted. The study demonstrates the rhetorical and poetic significance not only for the conceptualisation of street art actions but also for their transmedia projection. The final contribution presents six key ideas to be considered prior to designing such interventions.